2010
DOI: 10.1093/hmg/ddq494
|View full text |Cite
|
Sign up to set email alerts
|

NPHP4 is necessary for normal photoreceptor ribbon synapse maintenance and outer segment formation, and for sperm development

Abstract: Nephronophthisis (NPHP) is an autosomal recessive kidney disease that is often associated with vision and/or brain defects. To date, 11 genes are known to cause NPHP. The gene products, while structurally unrelated, all localize to cilia or centrosomes. Although mouse models of NPHP are available for 9 of the 11 genes, none has been described for nephronophthisis 4 (Nphp4). Here we report a novel, chemically induced mutant, nmf192, that bears a nonsense mutation in exon 4 of Nphp4. Homozygous mutant Nphp4(nmf1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 51 publications
5
75
0
Order By: Relevance
“…There have been discrepancies between human ciliopathies and their respective mouse models, which are likely due to differences in species and/or functional nature of the mutation (Hall et al, 2013;Jiang et al, 2008;Mykytyn et al, 2004;Won et al, 2011). For most ciliopathies, mouse models fail to completely recapitulate the human phenotype.…”
Section: Research Articlementioning
confidence: 99%
“…There have been discrepancies between human ciliopathies and their respective mouse models, which are likely due to differences in species and/or functional nature of the mutation (Hall et al, 2013;Jiang et al, 2008;Mykytyn et al, 2004;Won et al, 2011). For most ciliopathies, mouse models fail to completely recapitulate the human phenotype.…”
Section: Research Articlementioning
confidence: 99%
“…BBS knockouts manifest a broad syndromic phenotype which includes retinal degeneration, obesity, development of renal cysts, and olfactory abnormalities, among others. Deletion of the nephrocystin-4 gene (Nphp4) leads to infertility caused by sperm immobility paired with retina degeneration (Won et al, 2011), while deletion of nephrocystin-1 is associated with defects in spermiogenesis at much earlier steps (Jiang et al, 2008). Here we show that Cetn1 2/2 spermatid development is affected after the cap phase, namely at the transition from late acrosome phase to the early maturation phase of spermiogenesis, producing an altered rearrangement of the two centrioles and the centriolar adjunct, the effects of which manifest later as dysmorphic spermatid heads and tails.…”
Section: Yeastmentioning
confidence: 99%
“…A study of Nphp4-mutant mice has shown that Nphp4 is necessary for normal photoreceptor formation and maintenance as well as sperm development (Won et al, 2011). In zebrafish, nphp4 morphants exhibit classic ciliary phenotypes, including abnormal body curvature and pronephric cysts (Burcklé et al, 2011;Slanchev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…LAP-tagged NPHP4 in IMCD3 cells is present at sites of cell-cell contact and at the base of the primary cilium, specifically in the transition zone (Sang et al, 2011). Others have reported the presence of NPHP4 in the transition zone of cultured mouse renal epithelial cells (Shiba et al, 2010) and in the connecting ciliuma greatly elongated transition zone -of mouse photoreceptor cells (Roepman et al, 2005;Patil et al, 2012;Won et al, 2011). In Chlamydomonas reinhardtii, NPHP4 was identified in a proteomic study of basal bodies, which included the transition zone (Keller et al, 2005).…”
Section: Introductionmentioning
confidence: 99%